EFFECT OF E-TEACHING ON ANXIETY IN HIGH SCHOOL TEACHERS (International Journal of Food and Nutritional Sciences, 2022)
The objective of this study was to assess the impact of e-teaching on anxiety in high school teachers. To conduct the study 800 high school teachers from the Raipur district of Chhattisgarh were selected. This group is evenly divided between government and non-government schools, with 400 teachers from each category. Stratified random sampling was used for the selection of the sample. A pre-validated questionnaire was utilized to evaluate the e-teaching proficiency of high school teachers. The anxiety in selected high school teachers was measured through Sinha and Sinha's (2007) comprehensive anxiety test. A negative and significant correlation was found between high school teachers' e-teaching proficiency and their anxiety, with a correlation coefficient of r = -0.298, which was statistically significant at the 0.01 level. The coefficient of determination (R² = 0.11) suggests that about 11% of the variation in anxiety can be attributed to e-teaching proficiency among high school teachers and as high school teachers’ proficiency in e-teaching increases, their anxiety also tends to decrease significantly. Similarly, a significant but negative correlation was observed in a group of govt. and non-govt. high school teachers. It was concluded that enhancing e-teaching skills may therefore serve as a valuable tool for reducing anxiety among teachers, allowing them to feel more confident and comfortable with digital teaching methods